A virtually supervised exercise program improved fitness and mental wellness in healthy and comorbidity older adult individuals during the COVID-19 pandemic - Canton Martínez, Ermilo (2024)
Background: The COVID-19 pandemic affected older adults worldwide. Sedentary older adults experienced more severe adverse health effects due to their shelter-in-place. Physical activity was strongly recommended during periods of social distancing. The present study evaluated the impact of a virtually supervised exercise program on the physical fitness and mental health of Mexican older adults during the pandemic’s lockdown. Methods: Participants were 44 older adults who were assigned to one of four physical fitness groups: a healthy control group (Ctrl-H, n = 15), a comorbidity control group (Ctrl-COM, n = 9), an exercise group without comorbidities (Exe-H, n = 11), and an exercise group with comorbidities (Exe-COM, n = 9). The participants engaged in a 60-min, virtually-supervised concurrent exercise session three times/week for 12 weeks. Fitness was measured using the online Senior Fitness Tests and the 4-m Gait Speed Test. Mental health was evaluated through virtual interviews using the Hamilton Depression Rating Scale, the Geriatric Depression Scale, and the Connor-Davidson Resilience Scale. Within-subject pre vs. post-intervention comparisons tested for significant differences, between-groups and over time. Results: Significant interactions were found in the scores of the Geriatric Depression Scale (p ≤ 0.0001; ηp2 = 0.35), the Hamilton Depression Scale (p ≤ 0.0001; ηp2 = 0.35), resilience scores (p ≤ 0.0001; ηp2 = 0.46), lower-body strength (p ≤ 0.0001; ηp2 = 0.32), timed up-and-go test (p = 0.018; ηp2 = 0.18), the 6MWT distance scores (p ≤ 0.0001; ηp2 = 0.39), and the 4-m gait speed test scores (p = 0.011; ηp2 = 0.20). Conclusion: A long-term virtually-supervised exercise program conducted during the COVID-19 lockdown period led to marked improvements in both the fitness and mental health of older Mexican adults. Comorbidities did not diminish these benefits. These findings provide empirical support for online exercise programs in the daily routines of older adults to make clinically meaningful improvements in both physical and mental well-being.